Pengaruh Komitmen Afektif Terhadap Organizational Citizenship Behavior Pada Pekerja Milenial Di Indonesia - Muchtadin (LPPM STIA Lancang Kuning Dumai, 2024)
Organizational Citizenship Behavior (OCB) plays an important role in increasing the effectiveness of organizations that employ millennial workers. This research aims to determine the influence of affective commitment on aspects of organizational citizenship behavior such as altruism, conscientiousness, sportsmanship, courtesy and civic virtue. The respondents were 100 millennial workers in Indonesia who were taken using convenience sampling. The method for analyzing data was carried out using PLS SEM. The research results found that affective commitment had a positive effect on all dimensions of OCB such as altruism, prudence, sportsmanship, courtesy and civic virtue. Future research can limit workers of a certain gender, using the mediation of knowledge sharing and the moderation of emotional intelligence on the relationship between affective commitment and OCB in millennial workers. This research contributes to increasing OCB dimensions through affective commitment in millennial generation workers.